The FIND-CKD study–a randomized controlled trial of intravenous iron versus oral iron in non-dialysis chronic kidney disease patients: background and rationale - Macdougall, Iain C.; Bock, Andreas; Carrera, Fernando; Eckardt, Kai-Uwe; Gaillard, Carlo; Van Wyck, David; Roubert, Bernard; Cushway, Timothy; Roger, Simon D. (Nephrology Dialysis Transplantation, 2014)
Rigorous data are sparse concerning the optimal route of administration and dosing strategy for iron therapy with or without concomitant erythropoiesis-stimulating agent (ESA) therapy for the management of iron deficiency anaemia in patients with non-dialysis dependent chronic kidney disease (ND-CKD).FIND-CKD was a 56-week, open-label, multicentre, prospective, randomized three-arm study (NCT00994318) of 626 patients with ND-CKD and iron deficiency anaemia randomized to (i) intravenous (IV) ferric carboxymaltose (FCM) at an initial dose of 1000 mg iron with subsequent dosing as necessary to target a serum ferritin level of 400-600 µg/L (ii) IV FCM at an initial dose of 200 mg with subsequent dosing as necessary to target serum ferritin 100-200 µg/L or (iii) oral ferrous sulphate 200 mg iron/day. The primary end point was time to initiation of other anaemia management (ESA therapy, iron therapy other than study drug or blood transfusion) or a haemoglobin (Hb) trigger (two consecutive Hb values <10 g/dL without an increase of >= 0.5 g/dL).The background, rationale and study design of the trial are presented here. The study has been completed and results are expected in late 2013.FIND-CKD was the longest randomized trial of IV iron therapy to date. Its findings will address several unanswered questions regarding iron therapy to treat iron deficiency anaemia in patients with ND-CKD. It was also the first randomized trial to utilize both a high and low serum ferritin target range to adjust IV iron dosing, and the first not to employ Hb response as its primary end point.
EVALuna2:3644